Mainstreaming and misfitting: Exploring disability and its intersection with gender in online disability awareness-raising videos - Christensen-Strynø, Maria Bee (MedieKultur: Journal of media and communication research, 2016)
This article investigates how the concepts of ‘mainstreaming’ and ‘misfitting’ become useful analytical tools for analyzing visual media representations of disability. The analysis deals with two videos from online awareness-raising campaigns about disability, and the aim is to show that disability intersects with gender in ways that have significant consequences for how bodily expressions are negotiated. Media representations of both disability and gender have become more visible but are rarely studied together. When they are, it is rarely from a vantage point in disability experience. Therefore, I stress the importance of applying intersectional approaches specifically to disability and suggest a methodological framework composed of two contrasting movements: mainstreaming (as a reference point of striving for normalization in visual media representation) as opposed to misfitting (as a critical position that applies to disability and its intersection with gender). The analyses of the videos show how these positions are at play through sometimes very subtle capacities in which gender interferes with the processes of mainstreaming and stabilizing disability, or attempts are made to accommodate misfit positions by challenging and transgressing traditional notions of disabled and gendered embodiment.